Steel material

A steel material with a tailored chemical composition and microstructure addresses the issue of hydrogen embrittlement in bolts by forming fine MC carbides, enhancing their resistance to hydrogen-induced fractures.

JP2025062918APending Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172284
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Bolts with high strength are susceptible to hydrogen embrittlement, which can cause delayed fractures, and existing steel materials for bolts do not adequately address this issue.

Method used

A steel material with a specific chemical composition and microstructure, including 0.30-0.50% C, 0.01-0.30% Si, 0.10-1.50% Mn, 0.01-0.50% V, 2.50-3.50% Mo, and a microstructure with 90% hard structure and fine MC carbides, is developed to reduce hydrogen embrittlement susceptibility.

Benefits of technology

The steel material effectively reduces the susceptibility to hydrogen embrittlement in bolts, ensuring high strength and durability by trapping hydrogen in fine MC carbides, thereby preventing fractures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062918000001
    Figure 2025062918000001
  • Figure 2025062918000002
    Figure 2025062918000002
  • Figure 2025062918000003
    Figure 2025062918000003
Patent Text Reader

Abstract

To provide a steel material capable of reducing the hydrogen embrittlement susceptibility of a bolt.SOLUTION: A steel materials includes, by mass%, C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Mo: more than 2.50-3.50%, V: 0.01-0.50%, Al: 0.005-0.100%, N: 0.0010-0.0300% and the remainder consisting of Fe and impurities. The area rate of a hard structure is 90% or more; a Vickers hardness is 250-450HV; the number density of cementite in the hard structure is 4.0 pieces / μm2 or more; the number percentage of the cementite having an area of 0.0005-0.0100 μm2 in a plurality of cementites in the hard structure is 50.0% or more; the sample standard deviation of the area of the plurality of cementites in the hard structure is 0.070 μm2 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to steel materials, and more particularly to steel materials that can be used as materials for bolts. [Background technology]

[0002] Bolts are used in industrial machinery, automobiles, buildings such as bridges, etc. In recent years, with the increasing performance of industrial machinery and automobiles and the increasing size of buildings, etc., there is a demand for bolts with higher strength.

[0003] Bolts with high strength may have high susceptibility to hydrogen embrittlement. Hydrogen embrittlement is a cause of delayed fracture of bolts. Therefore, high strength bolts are required to have low susceptibility to hydrogen embrittlement.

[0004] WO 2020 / 162616 (Patent Document 1) proposes a steel material for bolts having high strength and low susceptibility to hydrogen embrittlement.

[0005] The steel material disclosed in Patent Document 1 contains, in mass%, 0.35-0.45% C, 0.02-0.10% Si, 0.20-0.84% ​​Mn, 0.60-1.15% Cr, 0.30-0.50%, 0.25-0.99% Mo, 0.010-0.100%, 0.0010-0.0150%, 0.015% or less P, 0.015% or less S, and the balance: Fe and impurities, and satisfies the following formula (1) and the following formula (2). 0.48≦Mo / 1.4+V<1.10 (1) 0.80 <Mo / V<3.00 (2) In this steel, the Mo content and V content in the chemical composition are adjusted to satisfy formulas (1) and (2). This makes it easier for MC carbides to disperse in bolts manufactured using this steel as a material. As a result, the hydrogen embrittlement susceptibility of the bolt is reduced. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2020 / 162616 Summary of the Invention [Problem to be solved by the invention]

[0007] Bolts manufactured using the steel material disclosed in Patent Document 1 have low susceptibility to hydrogen embrittlement. However, the hydrogen embrittlement susceptibility of bolts manufactured using the steel material may be reduced by a means other than that of Patent Document 1.

[0008] An object of the present disclosure is to provide a steel material that, when used as a material for a bolt, can reduce the hydrogen embrittlement susceptibility of the bolt. [Means for solving the problem]

[0009] The steel material according to the present disclosure comprises, in mass%, C: 0.30-0.50%, Si: 0.01 to 0.30%, Mn: 0.10-1.50%, P:0.030% or less, S: 0.030% or less, Cr: 0.01 to 0.30%, Mo: over 2.50 to 3.50%, V: 0.01 to 0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, The balance is Fe and impurities. The area ratio of hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV. 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 / μm or more 2 or more, and among the plurality of cementite in the hard structure, 0.0005 to 0.0100 μm 2The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 The following is the result.

[0010] The steel material according to the present disclosure comprises, in mass%, C: 0.30-0.50%, Si: 0.01 to 0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01 to 0.30%, Mo: over 2.50 to 3.50%, V: 0.01 to 0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, Further, it contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The area ratio of hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV. 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 / μm or more 2 or more, and among the plurality of cementite in the hard structure, 0.0005 to 0.0100 μm 2 The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 The following is the result. [Group 1] Cu: 0.40% or less, Ni: 0.40% or less, B: 0.0100% or less, Zr: 0.300% or less, Hf: 0.100% or less, Ta: 0.100% or less, and W: 0.200% or less, one or more selected from the group consisting of [Group 2] Ti: 0.100% or less, and Nb: 0.100% or less, one or more selected from the group consisting of [Group 3] Ca: 0.0050% or less, and Mg: 0.0050% or less, one or more selected from the group consisting of [Group 4] Bi: 0.020% or less, and Te: 0.010% or less, one or more selected from the group consisting of Effect of the Invention

[0011] When the steel material according to the present disclosure is used as a material for a bolt, it is possible to reduce the hydrogen embrittlement susceptibility of the bolt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present inventors have conducted research into steel materials that, when used as a bolt material, can reduce the hydrogen embrittlement susceptibility of the bolt. As a result, the present inventors have obtained the following findings.

[0013] First, the inventors of the present invention investigated, from the viewpoint of chemical composition, steel materials that can be used as bolt materials and that can reduce the hydrogen embrittlement susceptibility of bolts. As a result, the inventors of the present invention found that the steel materials are, in mass%, C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Al: 0.005-0.100%, N: 0.0010-0.0300%, Cu: 0-0.40%, Ni: 0-0.40%, B: 0-0.0100%, Zr: 0-0.300%, Hf: 0-0.100%, It was considered that a steel material having a chemical composition containing Ta: 0-0.100%, W: 0-0.200%, Ti: 0-0.100%, Nb: 0-0.100%, Ca: 0-0.0050%, Mg: 0-0.0050%, Bi: 0-0.020%, and Te: 0-0.010%, with the balance being Fe and impurities, may be able to reduce the hydrogen embrittlement susceptibility of a bolt when used as the material for the bolt.

[0014] The inventors further investigated means for reducing the hydrogen embrittlement susceptibility from the viewpoint of the microstructure of the bolt having the above-mentioned chemical composition, and as a result, they found that the hydrogen embrittlement susceptibility of the bolt can be reduced by dispersing a large number of fine MC type carbides in the bolt.

[0015] Therefore, the inventors considered that if Mo and V were further added to the above-mentioned chemical composition, fine MC carbides would be formed in the bolt, and the hydrogen embrittlement susceptibility of the bolt would be reduced. Therefore, the inventors further studied the chemical composition of the steel material, taking into consideration the generation of MC carbides during the bolt manufacturing process. As a result, it was found that if the steel material of this embodiment satisfies the chemical composition of the following characteristic 1, when a bolt is manufactured using the steel material, the hydrogen embrittlement susceptibility of the bolt will be reduced to a certain degree.

[0016] (Feature 1) The chemical composition, in mass%, is C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Mo: over 2.50-3.50%, V: 0.01-0.50%, Al: 0.005-0.100%, N: 0.0010-0.0300%, Cu: 0-0.40%, Ni: 0-0.40%, B: 0-0.0100%, Zr: 0-0.300%, Hf: 0-0.100%, Ta: 0-0.100%, W: 0-0.200%, Ti: 0-0.100%, Nb: 0-0.100%, Ca: 0-0.0050%, Mg: 0-0.0050%, Bi: 0-0.020%, and Te: 0-0.010%, with the balance being Fe and impurities.

[0017] However, even with a steel material having the chemical composition of Feature 1, there are cases where the hydrogen embrittlement susceptibility of the bolt cannot be sufficiently reduced. Therefore, the present inventors have investigated means for further reducing the hydrogen embrittlement susceptibility of the bolt. As a result, the following findings have been obtained.

[0018] In the case of a steel material having a chemical composition that satisfies Feature 1, cementite is generated in the steel material. Furthermore, in the manufacturing process of a bolt using the above-mentioned steel material as a material, the steel material is subjected to spheroidizing annealing, quenching, and tempering. As a result, the above-mentioned fine MC type carbides containing Mo and / or V are generated in the bolt.

[0019] In order to generate fine MC carbides in the bolt, it is preferable that the cementite in the steel material is sufficiently dissolved during quenching. The cementite in the steel material before quenching contains Mo and V. If the cementite in the steel material is layered (i.e., if the cementite is part of pearlite (lamella pearlite)), the cementite in the steel material is not sufficiently dissolved during quenching in the bolt manufacturing process. In this case, even if tempering is performed, a sufficient amount of fine MC carbides is not generated.

[0020] Therefore, in the steel material of this embodiment, the microstructure is designed to satisfy the following characteristic 2. (Feature 2) The area ratio of the hard structure in the microstructure is 90% or more, and the Vickers hardness of the steel material is 250 to 450HV. Here, the hard structure is a structure made of ferrite containing carbides, and does not contain pearlite, which is a lamellar structure of carbides and ferrite. Such a hard structure is sometimes called bainite.

[0021] In the microstructure of a steel material having a chemical composition that satisfies the characteristic 1, if the area ratio of the hard structure is 90% or more and the Vickers hardness of the steel material is 250 to 450HV, the cementite in the microstructure is not layered but is almost granular. Granular cementite is more likely to be fully dissolved during quenching than layered cementite in pearlite. Therefore, the microstructure of the steel material is made to be substantially a hard structure.

[0022] In the microstructure of the steel material of this embodiment, when a structure other than pro-eutectoid ferrite and pearlite is defined as a "hard structure", if the area ratio of the hard structure in the microstructure is 90% or more and the Vickers hardness of the steel material is 250 to 450HV, the microstructure of the steel material is substantially a hard structure. Therefore, the steel material of this embodiment is specified as Feature 2.

[0023] As described above, the present inventors considered that if a steel material satisfies Features 1 and 2, when a bolt is manufactured using the steel material as a material, the hydrogen embrittlement susceptibility of the bolt can be sufficiently reduced. However, even if the steel material satisfies Features 1 and 2, there were still cases where the hydrogen embrittlement susceptibility of the bolt manufactured using the steel material as a material could not be sufficiently reduced. Therefore, as a result of further investigation, the present inventors obtained the following findings.

[0024] Even if the microstructure of the steel is substantially hard and the cementite in the steel is granular, the amount of fine MC carbides produced in the bolt after tempering is affected by the number density of cementite in the steel and the grain size distribution of cementite. If the number density of cementite in the steel is low, the sites for producing MC carbides are not sufficiently obtained. Even if the average grain size of cementite in the steel is small, if the grain size distribution of cementite is broad, the size of the cementite in the steel varies. In this case, the amount of V and Mo contained in the cementite of large size is larger than that of the cementite of small size. Therefore, even if the cementite in the steel is sufficiently dissolved by quenching, V and Mo are concentrated in the microregion where the cementite of large size is dissolved compared to other microregions (regions where the cementite of small size is dissolved). Therefore, even if the average grain size of cementite is small, if the grain size distribution of cementite is broad, V and Mo enriched regions occur locally during quenching due to the large size of cementite. In this case, it is difficult to generate a sufficient amount of fine MC type carbides during tempering. Therefore, in bolts manufactured using steel as a material, sufficient hydrogen trapping sites cannot be secured. As a result, the hydrogen embrittlement susceptibility of the bolt is not sufficiently reduced.

[0025] Therefore, in the steel material of this embodiment, in order to suppress the generation of V and Mo concentrated regions during quenching, the number density of cementite in the steel material is increased as much as possible. Furthermore, the number ratio of fine cementite among a plurality of cementite particles is increased as much as possible. Furthermore, in order to suppress the variation in the size of cementite, the grain size distribution of cementite is made sharp. Specifically, the steel material satisfying the characteristics 1 and 2 is made to also satisfy the following characteristic 3.

[0026] (Feature 3) 0.0005μm in hard tissue 2 The number density ND of cementite having an area of ​​4.0 / μm 2 or more, and 0.0005 μm in hard tissue 2Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the areas of multiple cementites having an area of ​​0.070 μm or more 2 The following is the result.

[0027] In this case, the steel material contains a sufficient amount of cementite. Furthermore, the cementite is sufficiently fine, and the grain size distribution of the cementite is sufficiently sharp. In other words, the variation in the size of the cementite is sufficiently suppressed. Therefore, during quenching in the manufacturing process of manufacturing a bolt using the steel material as a raw material, the cementite is sufficiently dissolved, and V and Mo concentrated regions are unlikely to occur. As a result, the hydrogen embrittlement susceptibility of the bolt is sufficiently low.

[0028] The above mechanism is a guess. Therefore, a bolt manufactured using the steel material of this embodiment as a material may have a sufficiently low hydrogen embrittlement susceptibility due to a mechanism different from the above. However, as shown in the examples described later, when a bolt is manufactured using a steel material that satisfies Features 1 to 3, the hydrogen embrittlement susceptibility of the bolt is sufficiently low.

[0029] The steel material according to this embodiment, which has been completed based on the above findings, has the following configuration.

[0030] [1] In mass%, C: 0.30-0.50%, Si: 0.01 to 0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01 to 0.30%, Mo: over 2.50 to 3.50%, V: 0.01 to 0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, The balance is Fe and impurities. The area ratio of hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV. 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 / μm or more 2 or more, and among the plurality of cementite in the hard structure, 0.0005 to 0.0100 μm 2 The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 Below is the Steel material.

[0031] [2] In mass%, C: 0.30-0.50%, Si: 0.01 to 0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01 to 0.30%, Mo: over 2.50 to 3.50%, V: 0.01 to 0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, Further, it contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The area ratio of hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV. 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 / μm or more 2 or more, and among the plurality of cementite in the hard structure, 0.0005 to 0.0100 μm 2The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 Below is the Steel material. [Group 1] Cu: 0.40% or less, Ni: 0.40% or less, B: 0.0100% or less, Zr: 0.300% or less, Hf: 0.100% or less, Ta: 0.100% or less, and W: 0.200% or less, one or more selected from the group consisting of [Group 2] Ti: 0.100% or less, and Nb: 0.100% or less, one or more selected from the group consisting of [Group 3] Ca: 0.0050% or less, and Mg: 0.0050% or less, one or more selected from the group consisting of [Group 4] Bi: 0.020% or less, and Te: 0.010% or less, one or more selected from the group consisting of

[0032] [3] [2] The steel material according to the present invention, Containing the first group, Steel material.

[0033] [4] The steel material according to [2] or [3], Containing the second group, Steel material.

[0034] [5] The steel material according to any one of [2] to [4], Containing the third group, Steel material.

[0035] [6] The steel material according to any one of [2] to [5], Containing the fourth group, Steel material.

[0036] The steel material of this embodiment will be described in detail below. Note that "%" for elements means mass % unless otherwise specified.

[0037] [Features of the steel material of this embodiment] The steel material of this embodiment has the following characteristics. (Feature 1) The chemical composition, in mass%, is C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10-1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Mo: over 2.50-3.50%, V: 0.01-0.50%, Al: 0.005-0.100%, N: 0.0010-0.0300%, Cu: 0-0.40%, Ni: 0-0.40%, B: 0-0.0100%, Zr: 0-0.300%, Hf: 0-0.100%, Ta: 0-0.100%, W: 0-0.200%, Ti: 0-0.100%, Nb: 0-0.100%, Ca: 0-0.0050%, Mg: 0-0.0050%, Bi: 0-0.020%, and Te: 0-0.010%, with the balance being Fe and impurities. (Feature 2) The area ratio of hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV. (Feature 3) 0.0005μm in hard tissue 2 The number density ND of cementite having an area of ​​4.0 / μm 2 or more, and 0.0005 μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the area of ​​multiple cementites having an area of ​​0.070 μm or more 2 The following is the result. Features 1 to 3 will be explained below.

[0038] [(Feature 1) Chemical composition] The chemical composition of the steel material of this embodiment contains the following elements.

[0039] C: 0.30-0.50% Carbon (C) improves the hardenability of the steel material and increases the strength of the bolt. C also forms cementite and increases the number density ND of the cementite, which will be described later. This reduces the hydrogen embrittlement susceptibility of the bolt. If the C content is less than 0.30%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the C content exceeds 0.50%, the hydrogen embrittlement susceptibility of the bolt increases even if the contents of other elements are within the ranges of this embodiment. Therefore, the C content is 0.30 to 0.50%. The lower limit of the C content is preferably 0.32%, and more preferably 0.35%. The upper limit of the C content is preferably 0.48%, and more preferably 0.45%.

[0040] Silicon: 0.01 to 0.30% Silicon (Si) improves the hardenability of steel material and increases the strength of the bolt. If the Si content is less than 0.01%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Si content exceeds 0.30%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Si content is 0.01 to 0.30%. The lower limit of the Si content is preferably 0.02%, and more preferably 0.03%. The upper limit of the Si content is preferably 0.25%, more preferably 0.20%, and further preferably 0.15%.

[0041] Mn: 0.10-1.50% Manganese (Mn) improves the hardenability of steel material and increases the strength of the bolt. If the Mn content is less than 0.10%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Mn content exceeds 1.50%, the hydrogen embrittlement susceptibility of the bolt increases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Mn content is 0.10 to 1.50%. The lower limit of the Mn content is preferably 0.15%, and more preferably 0.20%. The upper limit of the Mn content is preferably 1.30%, more preferably 1.20%, and further preferably 1.10%.

[0042] P:0.030% or less Phosphorus (P) is an impurity. In other words, the lower limit of the P content is more than 0%. If the P content exceeds 0.030%, P segregates at grain boundaries. As a result, even if the contents of other elements are within the ranges of this embodiment, the hydrogen embrittlement susceptibility of the bolt increases. Therefore, the P content is 0.030% or less. The P content is preferably as low as possible. However, excessive reduction in the P content significantly increases the production cost. Therefore, in consideration of industrial production, the lower limit of the P content is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%. The upper limit of the P content is preferably 0.025%, and more preferably 0.020%.

[0043] S: 0.030% or less Sulfur (S) is an impurity. In other words, the lower limit of the S content is more than 0%. If the S content exceeds 0.030%, S segregates at grain boundaries. As a result, even if the contents of other elements are within the ranges of this embodiment, the hydrogen embrittlement susceptibility of the bolt increases. Therefore, the S content is 0.030% or less. The S content is preferably as low as possible. However, excessive reduction in the S content significantly increases the production cost. Therefore, in consideration of industrial production, the lower limit of the S content is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%. The upper limit of the S content is preferably 0.025%, and more preferably 0.020%.

[0044] Cr: 0.01~0.30% Chromium (Cr) improves the hardenability of steel material and increases the strength of the bolt. Cr also improves the temper softening resistance of the steel material and increases the strength of the bolt. If the Cr content is less than 0.01%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Cr content is 0.30% or less, on the premise that the contents of other elements are within the ranges of this embodiment, the penetration of hydrogen into the steel material is sufficiently suppressed, and as a result, the hydrogen embrittlement susceptibility of the bolt is sufficiently suppressed. Therefore, the Cr content is 0.01 to 0.30%. The lower limit of the Cr content is preferably 0.03%, and more preferably 0.05%. The upper limit of the Cr content is preferably 0.25%, more preferably 0.20%, and further preferably 0.15%.

[0045] Mo: Over 2.50 to 3.50% Molybdenum (Mo) increases the temper softening resistance of steel materials and increases the strength of bolts. Mo also concentrates in MC carbides and enhances the hydrogen trapping function of MC carbides. As a result, Mo reduces the hydrogen embrittlement susceptibility of bolts. If the Mo content exceeds 2.50%, the above effects are sufficiently obtained. On the other hand, if the Mo content is 3.50% or less, sufficient cold forgeability can be obtained in the steel material, provided that the contents of other elements are within the ranges of this embodiment. Therefore, the Mo content is more than 2.50% to 3.50%. The lower limit of the Mo content is preferably 2.51%, more preferably 2.55%, more preferably 2.60%, more preferably 2.70%, more preferably 2.71%, more preferably 2.72%, more preferably 2.75%, and more preferably 2.80%. The upper limit of the Mo content is preferably 3.40%, and more preferably 3.30%.

[0046] V: 0.01 to 0.50% Vanadium (V) forms MC type carbides together with Mo to reduce the hydrogen embrittlement susceptibility of the bolt. If the V content is less than 0.01%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the V content exceeds 0.50%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the V content is 0.01 to 0.50%. The lower limit of the V content is preferably 0.03%, and more preferably 0.05%. The upper limit of the V content is preferably 0.45%, more preferably 0.40%, and further preferably 0.35%.

[0047] Al: 0.005 to 0.100% Aluminum (Al) deoxidizes steel during the steelmaking process. Furthermore, Al combines with N to form Al nitrides. The Al nitrides suppress grain coarsening through a pinning effect during the quenching process in bolt manufacturing. As a result, the bolt is less susceptible to hydrogen embrittlement. If the Al content is less than 0.005%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the Al content exceeds 0.100%, coarse Al nitrides are generated. The coarse Al nitrides become the starting points of cracks. Therefore, even if the contents of other elements are within the ranges of this embodiment, the cold forgeability of the steel material is reduced. Therefore, the Al content is 0.005 to 0.100%. The lower limit of the Al content is preferably 0.006%, more preferably 0.007%, and further preferably 0.008%. The upper limit of the Al content is preferably 0.090%, more preferably 0.080%, and further preferably 0.070%. In the chemical composition of the steel material of this embodiment, the Al content means the total Al content.

[0048] N: 0.0010~0.0300% Nitrogen (N) combines with Al to form Al nitrides. The Al nitrides suppress the coarsening of crystal grains by the pinning effect during the quenching process in the manufacture of the bolt. As a result, the bolt is less susceptible to hydrogen embrittlement. If the N content is less than 0.0010%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the ranges of this embodiment. On the other hand, if the N content exceeds 0.0300%, coarse nitrides are generated. The coarse nitrides become the starting points of cracks. Therefore, even if the contents of other elements are within the ranges of this embodiment, the cold forgeability of the steel material is reduced. Therefore, the N content is 0.0010 to 0.0300%. The lower limit of the N content is preferably 0.0020%, more preferably 0.0025%, further preferably 0.0030%, and further preferably 0.0051%. The upper limit of the N content is preferably 0.0290%, more preferably 0.0280%, more preferably 0.0270%, more preferably 0.0250%, more preferably 0.0200%, more preferably 0.0150%, and more preferably 0.0100%.

[0049] The balance of the chemical composition of the steel material of the present embodiment is composed of Fe and impurities. Here, the impurities in the chemical composition refer to those that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and are not intentionally contained, but are allowed within a range that does not adversely affect the steel material of the present embodiment.

[0050] Examples of impurities other than those mentioned above are as follows: O: 0.0030% or less Sn: 0.100% or less Pb:0.090% or less Sb: 0.050% or less Zn: 0.050% or less Co:0.050% or less Rare earth elements (REM): 0.020% or less The content of each of these impurity elements may be 0%.

[0051] [Optional Elements] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of Cu, Ni, B, Zr, Hf, Ta, W, Ti, Nb, Ca, Mg, Bi, and Te in place of a portion of Fe. All of these elements are optional elements and may not be contained. These optional elements will now be described.

[0052] [Group 1: Cu, Ni, B, Zr, Hf, Ta and W] The chemical composition of the steel material of this embodiment may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Cu, Ni, B, Zr, Hf, Ta, and W. All of these elements are optional elements and may not be contained. When contained, Cu, Ni, B, Zr, Hf, Ta, and W improve the hardenability of the steel material and increase the strength of the bolt.

[0053] Cu: 0.40% or less Copper (Cu) is an optional element and may not be contained, that is, the Cu content may be 0%. When Cu is contained, that is, when the Cu content exceeds 0%, Cu increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of Cu is contained, the above effects can be obtained to a certain extent. However, if the Cu content exceeds 0.40%, even if the contents of other elements are within the ranges of this embodiment, the steel material becomes embrittled, and as a result, the hot workability of the steel material decreases. Therefore, the Cu content is 0 to 0.40%, and if contained, the Cu content is 0.40% or less. The lower limit of the Cu content is preferably 0.01%, more preferably 0.03%, and further preferably 0.05%. The upper limit of the Cu content is preferably 0.35%, more preferably 0.30%, and further preferably 0.25%.

[0054] Ni: 0.40% or less Nickel (Ni) is an optional element and may not be contained, that is, the Ni content may be 0%. When Ni is contained, that is, when the Ni content exceeds 0%, Ni increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of Ni is contained, the above effects can be obtained to a certain extent. However, if the Ni content exceeds 0.40%, even if the contents of other elements are within the ranges of this embodiment, the hardenability becomes excessively high, resulting in a deterioration in the hot workability of the steel material. Therefore, the Ni content is 0 to 0.40%, and if Ni is contained, the Ni content is 0.40% or less. The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%. The upper limit of the Ni content is preferably 0.35%, more preferably 0.30%, and further preferably 0.25%.

[0055] B: 0.0100% or less Boron (B) is an optional element and may not be contained, that is, the B content may be 0%. When B is contained, that is, when the B content is more than 0%, B improves the hardenability of the steel material and increases the strength of the bolt. B also suppresses the grain boundary segregation of P and reduces the hydrogen embrittlement susceptibility of the bolt. Even if even a small amount of B is contained, the above effects can be obtained to a certain extent. However, if the B content exceeds 0.0100%, coarse B nitrides are generated. The coarse B nitrides become the starting points of cracks. As a result, the cold forgeability of the steel material is reduced even if the contents of other elements are within the ranges of this embodiment. Therefore, the B content is 0 to 0.0100%, and if B is contained, the B content is 0.0100% or less. The lower limit of the B content is preferably 0.0001%, more preferably 0.0005%, and further preferably 0.0008%. The upper limit of the B content is preferably 0.0090%, more preferably 0.0080%, more preferably 0.0070%, more preferably 0.0060%, and even more preferably 0.0050%.

[0056] Zr: 0.300% or less Zirconium (Zr) is an optional element and may not be contained, that is, the Zr content may be 0%. When Zr is contained, that is, when the Zr content is more than 0%, Zr increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of Zr is contained, the above effects can be obtained to some extent. However, if the Zr content exceeds 0.300%, coarse Zr nitrides are generated, which become the starting points of cracks, and as a result, the cold forgeability of the steel material is reduced even if the contents of other elements are within the ranges of this embodiment. Therefore, the Zr content is 0 to 0.300%, and if contained, the Zr content is 0.300% or less. The lower limit of the Zr content is preferably 0.001%, more preferably 0.010%, and further preferably 0.020%. The upper limit of the Zr content is preferably 0.280%, more preferably 0.250%, more preferably 0.200%, more preferably 0.150%, and even more preferably 0.100%.

[0057] Hf:0.100% or less Hafnium (Hf) is an optional element and may not be contained, i.e., the Hf content may be 0%. When Hf is contained, that is, when the Hf content is more than 0%, Hf increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of Hf is contained, the above effects can be obtained to some extent. However, if the Hf content exceeds 0.100%, coarse Hf nitrides are generated, which become the starting points of cracks, and as a result, the cold forgeability of the steel material is reduced even if the contents of other elements are within the ranges of this embodiment. Therefore, the Hf content is 0 to 0.100%, and if contained, the Hf content is 0.100% or less. The lower limit of the Hf content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Hf content is preferably 0.080%, more preferably 0.070%, further preferably 0.060%, and further preferably 0.050%.

[0058] Ta:0.100% or less Tantalum (Ta) is an optional element and may not be contained, that is, the Ta content may be 0%. When Ta is contained, that is, when the Ta content exceeds 0%, Ta increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of Ta is contained, the above effects can be obtained to some extent. However, if the Ta content exceeds 0.100%, coarse Ta nitrides are generated, which become the starting points of cracks, and as a result, the cold forgeability of the steel material is reduced even if the contents of other elements are within the ranges of this embodiment. Therefore, the Ta content is 0 to 0.100%, and if contained, the Ta content is 0.100% or less. The lower limit of the Ta content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Ta content is preferably 0.080%, more preferably 0.070%, further preferably 0.060%, and further preferably 0.050%.

[0059] W: 0.200% or less Tungsten (W) is an optional element and may not be contained, that is, the W content may be 0%. When W is contained, that is, when the W content exceeds 0%, W increases the hardenability of the steel material and increases the strength of the bolt. Even if even a small amount of W is contained, the above effects can be obtained to a certain extent. However, if the W content exceeds 0.200%, even if the contents of other elements are within the ranges of this embodiment, the hardenability becomes excessively high, resulting in a decrease in the cold forgeability of the steel material. Therefore, the W content is 0 to 0.200%, and if W is contained, the W content is 0.200% or less. The lower limit of the W content is preferably 0.001%, more preferably 0.002%, and further preferably 0.010%. The upper limit of the W content is preferably 0.150%, more preferably 0.120%, and further preferably 0.100%.

[0060] [Group 2: Ti and Nb] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of Ti and Nb, instead of a part of Fe. All of these elements are optional elements and may not be contained. When contained, Ti and Nb form precipitates and refine the crystal grains. As a result, the hydrogen embrittlement susceptibility of the bolt is reduced.

[0061] Ti:0.100% or less Titanium (Ti) is an optional element and may not be contained, that is, the Ti content may be 0%. When Ti is contained, that is, when the Ti content is more than 0%, Ti forms fine precipitates such as Ti carbides and refines the grains. As a result, the bolt is less susceptible to hydrogen embrittlement. Even if Ti is contained even a small amount, the above effect can be obtained to some extent. However, if the Ti content exceeds 0.100%, coarse Ti nitrides are generated, which become the starting points of cracks, and as a result, the cold forgeability of the steel material is reduced even if the contents of other elements are within the ranges of this embodiment. Therefore, the Ti content is 0 to 0.100%, and if Ti is contained, the Ti content is 0.100% or less. The lower limit of the Ti content is preferably 0.001%, more preferably 0.003%, and further preferably 0.005%. The upper limit of the Ti content is preferably 0.090%, more preferably 0.080%, and further preferably 0.075%.

[0062] Nb: 0.100% or less Niobium (Nb) is an optional element and may not be contained, that is, the Nb content may be 0%. When Nb is contained, that is, when the Nb content is more than 0%, Nb forms fine precipitates such as Nb carbides and refines the grains. As a result, the hydrogen embrittlement susceptibility of the bolt is reduced. Even if even a small amount of Nb is contained, the above effect can be obtained to some extent. However, if the Nb content exceeds 0.100%, coarse Nb carbides are generated. The coarse Nb carbides become the starting points of cracks. As a result, even if the contents of other elements are within the ranges of this embodiment, the cold forgeability of the steel material is reduced. Therefore, the Nb content is 0 to 0.100%, and if Nb is contained, the Nb content is 0.100% or less. The lower limit of the Nb content is preferably 0.001%, more preferably 0.003%, further preferably 0.010%, and further preferably 0.020%. The upper limit of the Nb content is preferably 0.090%, more preferably 0.080%, and further preferably 0.070%.

[0063] [Group 3: Ca and Mg] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of Ca and Mg instead of a part of Fe. All of these elements are optional elements and may not be contained. When contained, Ca and Mg refine MnS in the steel material and reduce the hydrogen embrittlement susceptibility of the bolt.

[0064] Ca: 0.0050% or less Calcium (Ca) is an optional element and may not be contained, that is, the Ca content may be 0%. When Ca is contained, that is, when the Ca content is more than 0%, Ca refines MnS in the steel material and reduces the hydrogen embrittlement susceptibility of the bolt. Even if even a small amount of Ca is contained, the above effect can be obtained to some extent. However, if the Ca content exceeds 0.0050%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Ca content is 0 to 0.0050%, and if Ca is contained, the Ca content is 0.0050% or less. The lower limit of the Ca content is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0005%. The upper limit of the Ca content is preferably 0.0040%, and more preferably 0.0030%.

[0065] Mg: 0.0050% or less Magnesium (Mg) is an optional element and may not be contained, that is, the Mg content may be 0%. When Mg is contained, that is, when the Mg content is more than 0%, Mg refines MnS in the steel material and reduces the hydrogen embrittlement susceptibility of the bolt. Even if even a small amount of Mg is contained, the above effect can be obtained to some extent. However, if the Mg content exceeds 0.0050%, the cold forgeability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Mg content is 0 to 0.0050%, and if Mg is contained, the Mg content is 0.0050% or less. The lower limit of the Mg content is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0005%. The upper limit of the Mg content is preferably 0.0040%, and more preferably 0.0030%.

[0066] [Group 4: Bi and Te] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of Bi and Te, instead of a portion of Fe. All of these elements are optional elements and may not be contained. When contained, Bi and Te improve the machinability of the steel material.

[0067] Bi:0.020% or less Bismuth (Bi) is an optional element and may not be contained, that is, the Bi content may be 0%. When Bi is contained, that is, when the Bi content exceeds 0%, Bi enhances the machinability of the steel material. Even if even a small amount of Bi is contained, the above effect can be obtained to some extent. However, if the Bi content exceeds 0.020%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Bi content is 0 to 0.020%, and if Bi is contained, the Bi content is 0.020% or less. The lower limit of the Bi content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Bi content is preferably 0.018%, and more preferably 0.015%.

[0068] Te: 0.010% or less Tellurium (Te) is an optional element and may not be contained, that is, the Te content may be 0%. When Te is contained, that is, when the Te content exceeds 0%, Te enhances the machinability of the steel material. Even if even a small amount of Te is contained, the above effect can be obtained to some extent. However, if the Te content exceeds 0.010%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of this embodiment. Therefore, the Te content is 0 to 0.010%, and if contained, the Te content is 0.010% or less. The lower limit of the Te content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Te content is preferably 0.009%, and more preferably 0.008%.

[0069] [Feature 2: Microstructure of steel] The microstructure of the steel material of this embodiment has the following characteristics. (Feature 2) The area ratio of hard structure is 90% or more, and the Vickers hardness of the steel material is 250 to 450 HV. Here, the hard structure is a structure other than pro-eutectoid ferrite and pearlite, and is a structure made of ferrite containing carbides. Such a hard structure is sometimes called bainite.

[0070] The microstructure of the steel material of this embodiment is substantially a hard structure. The hard structure can be easily distinguished from structures other than the hard structure (pro-eutectoid ferrite and pearlite) by microstructure observation described later.

[0071] When the content of each element in the chemical composition is within the range of this embodiment, if the area ratio of the hard structure in the microstructure is 90% or more and the Vickers hardness of the microstructure of the steel material is 250 to 450 HV, the microstructure is substantially composed of a hard structure.

[0072] The steel material of this embodiment is subjected to a spheroidizing treatment during the manufacturing process of the bolt. As described above, the microstructure of the steel material of this embodiment is substantially a hard structure. Therefore, in the steel material after the spheroidizing treatment, the spheroidizing rate of cementite is increased. In this case, the cold forgeability of the steel material can be improved.

[0073] The lower limit of the area ratio of the hard structure in the microstructure of the steel material is preferably 92%, more preferably 94%, and further preferably 96%.

[0074] The Vickers hardness of the microstructure of the steel material is preferably 260HV at its lower limit, more preferably 270HV at its upper limit, and more preferably 280HV at its upper limit. The Vickers hardness of the microstructure of the steel material is preferably 440HV at its upper limit, more preferably 430HV at its upper limit, more preferably 420HV at its upper limit, and more preferably 410HV at its upper limit.

[0075] [Method of measuring the microstructure of steel] The microstructure of this embodiment can be measured by the following method. The cross section perpendicular to the longitudinal direction of the steel material is defined as the cross section. In the cross section, the center position of the radius connecting the central axis and the steel surface is defined as the "D / 4" position. D is the diameter of the cross section.

[0076] A sample is taken with the cross section (transverse section) perpendicular to the longitudinal direction of the steel material as the observation surface. The observation surface of the sample is the entire cross section perpendicular to the longitudinal direction of the steel material. In other words, the diameter of the observation surface of the sample is D. The observation surface of the sample is mirror-polished. The mirror-polished observation surface is etched at room temperature for 10 seconds using 3% nitric acid alcohol (Nital etching solution). On the etched observation surface, an observation field centered on an arbitrary point at a depth of D / 4 is set as observation field P1. From observation field P1, observation fields P2 to P4 are determined at 90° intervals around the central axis of the steel material. The area of ​​each observation field P1 to P4 is 90 μm × 120 μm. The four observation fields P1 to P4 centered on the D / 4 depth position are observed with a 1000x optical microscope.

[0077] In the observation field, the hard structure can be easily distinguished from the pro-eutectoid ferrite and pearlite by contrast. The pro-eutectoid ferrite is observed as a white region. In the observation at 1000x magnification, the pearlite is observed as a phase having a lamellar structure. The hard structure is observed as a region with a lower brightness than the ferrite. Therefore, the pro-eutectoid ferrite and the pearlite are identified based on the contrast. Specifically, in the observation at 1000x magnification, the white structure is recognized as the pro-eutectoid ferrite. In the observation at 1000x magnification, the structure in which the lamellae can be confirmed is recognized as the pearlite. In each observation field, the structure other than the pro-eutectoid ferrite and the pearlite is regarded as the hard structure.

[0078] Based on the identified pro-eutectoid ferrite and pearlite, the total area of ​​the pro-eutectoid ferrite and pearlite in the four observation fields P1 to P4 is determined. The total area of ​​the hard structure in the four observation fields is determined by subtracting the total area of ​​the pro-eutectoid ferrite and pearlite in the four observation fields from the total area of ​​the four observation fields P1 to P4. The area ratio (%) of the hard structure is determined based on the total area of ​​the hard structure in the four observation fields and the total area of ​​the four observation fields.

[0079] [Vickers hardness measurement method] The Vickers hardness of the microstructure of a steel material is determined by the following method. A sample is taken with the cross section (transverse section) perpendicular to the longitudinal direction of the steel material as the observation surface. The observation surface of the sample is the entire cross section perpendicular to the longitudinal direction of the steel material. In other words, the diameter of the observation surface of the sample is D. The observation surface is mirror-polished. On the observation surface after mirror polishing, an arbitrary measurement position at a depth of D / 4 in the radial direction from the surface of the steel material is set as measurement position P1. From measurement position P1, measurement positions P2 to P12 are determined at a 30° pitch around the center of the observation surface of the sample (i.e., equivalent to the center of the transverse section of the steel material). Vickers hardness is measured at measurement positions P1 to P12, which are the 12 D / 4 depth positions.

[0080] At each of the measurement positions P1 to P12, a Vickers hardness test is performed in accordance with JIS Z 2244-1:2020. The test force is 0.98 N. The arithmetic mean value of the hardness obtained at the 12 measurement positions is defined as the Vickers hardness (HV) of the microstructure of the steel material.

[0081] [(Feature 3) Cementite in steel] In the steel material of this embodiment, 0.0005 μm in the hard structure 2 The number density ND of cementite having an area of ​​4.0 / μm 2 or more, and 0.0005 μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the area of ​​multiple cementites having an area of ​​0.070 μm or more 2 The following is the result.

[0082] The steel material of this embodiment has a high V content and Mo content. Therefore, when this steel material is used to manufacture a bolt, many fine MC carbides containing Mo are formed by tempering after quenching during the manufacturing process. These fine MC carbides are likely to trap hydrogen. Therefore, the manufactured bolt has a high limit of hydrogen that leads to fracture. As a result, the bolt has a low susceptibility to hydrogen embrittlement.

[0083] In order to achieve the above effects, in the steel material from which the bolt is made, (1) the number density of cementite in the hard structure is increased, (2) the ratio of fine cementite among the multiple cementite particles in the hard structure is increased, and (3) the variation in the size of the cementite is suppressed to make the grain size distribution of the cementite sharp. These points will be explained below.

[0084] [Regarding the number density of cementite (above (1))] During the manufacturing process of a bolt made of steel, the higher the number density of cementite in the hard structure of the steel, the higher the number density of MC carbides in the bolt, and the more uniformly the MC carbides are dispersed in the bolt. As a result, the hydrogen embrittlement susceptibility of the bolt is sufficiently low. Specifically, in a steel that satisfies the above-mentioned characteristics 1 and 2, 2 The number density ND of cementite having an area of ​​4.0 / μm 2 If this is the case, the MC type carbides in the bolt are sufficiently finely dispersed, and the hydrogen embrittlement susceptibility of the bolt is sufficiently low.

[0085] The preferred lower limit of the number density ND is 4.2 pieces / μm 2 and more preferably 4.5 particles / μm 2 and more preferably 4.7 particles / μm 2 It is. The upper limit of the number density ND is not particularly limited. The preferred upper limit of the number density ND is 25.0 particles / μm 2 and more preferably 20.0 particles / μm 2 and more preferably 15.0 particles / μm 2 and more preferably 10.0 particles / μm 2 It is.

[0086] [Regarding the grain size distribution of cementite (above (2) and (3))] Even if the microstructure of a steel material satisfying Feature 1 is substantially bainite and the cementite is granular, the amount of fine MC carbides produced in the bolt after tempering is affected by the grain size distribution of the cementite. Specifically, even if the average grain size of multiple cementite particles in the steel material is small, if the grain size distribution of the cementite is broad, the sizes of the cementite particles in the steel material vary. In this case, the hydrogen embrittlement susceptibility of the bolt manufactured using the steel material cannot be sufficiently reduced.

[0087] 0.0005μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the area of ​​multiple cementites having an area of ​​0.070 μm or more 2 If the content is less than 100%, the cementite in the steel is sufficiently fine and the grain size distribution of the cementite is sufficiently sharp. In this case, during quenching in the manufacturing process of manufacturing a bolt using the steel as a raw material, the cementite is sufficiently dissolved and segregation regions of V and Mo are unlikely to occur. As a result, the hydrogen embrittlement susceptibility of the bolt is sufficiently low.

[0088] The lower limit of the number ratio NR is preferably 52.5%, more preferably 55.0%, and even more preferably 57.5%. The upper limit of the number ratio NR is not particularly limited. The upper limit of the number ratio NR is, for example, 100.0%, for example, 90.0%, for example, 85.0%, for example, 80.0%.

[0089] The preferred upper limit of the sample standard deviation σ is 0.065 μm. 2 and more preferably 0.063 μm 2 and more preferably 0.061 μm 2 It is.

[0090] [Method of measuring cementite number density ND, cementite number ratio NR and sample standard deviation σ of cementite area] 0.0005μm in hard tissue 2 The number density of cementite particles with an area of ​​0.0005 μm or more in the hard structure is ND. 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio of cementite with an area of ​​0.0005 μm and the number ratio of cementite with an area of ​​0.0005 μm in the hard structure 2 The sample standard deviation σ of the areas of a plurality of cementite particles having the above areas can be measured by the following method.

[0091] A sample is taken with a cross section (transverse section) perpendicular to the longitudinal direction of the steel material as the observation surface. The observation surface of the sample is the entire cross section perpendicular to the longitudinal direction of the steel material. In other words, the diameter of the observation surface of the sample is D. After polishing the observation surface of the sample, the observation surface is etched at room temperature for 20 seconds using a 6% picral etching solution (an etching solution containing 6 g of picric acid and 94 mL of ethanol). In the etched observation surface, an observation field centered on an arbitrary point at a depth of D / 4 is set as observation field P11. From observation field P11, observation fields P12 to P14 are determined at 90° intervals around the central axis of the steel material. The area of ​​each observation field P11 to P14 is 9 μm × 12 μm. Each of the observation fields P11 to P14 is observed at a magnification of 10,000 times using a field emission scanning electron microscope (FE-SEM), and particles (precipitates and inclusions) in the observation field are photographed to generate photographic images. The observation field is an area within the hard tissue.

[0092] Furthermore, in each of the above-mentioned observation fields, oxides and sulfides are identified by a known method using EDS (Energy Dispersive X-ray Spectroscopy) attached to the SEM. Specifically, particles with an O content of 5% or more by mass are identified as oxides, and particles with an O content of less than 5% and an S content of 5% or more by mass are identified as sulfides. Among the particles in the observation field, particles excluding oxides and sulfides are identified as cementite. The area of ​​the identified cementite is determined. The area of ​​the identified cementite can be determined, for example, by known image processing.

[0093] 0.0005μm identified in four observation fields 2 Based on the total number of cementite particles having an area of ​​100 μm or more and the total area of ​​the four observation fields, the number density ND (particles / μm 2 ) is required.

[0094] In addition, the specified 0.0005 μm 2 Among the cementite having an area of ​​0.0005 to 0.0100 μm or more,2 The ratio (%) of the total number of cementite particles is defined as the number ratio NR (%). 2 Based on the area of ​​each cementite having the above area, the sample standard deviation σ is calculated by the following formula.

[0095]

number

[0096] [Effects of the steel material of this embodiment] As described above, the steel material of this embodiment has the following configuration. (Feature 1) The content of each element in the chemical composition is within the range described in this embodiment. (Feature 2) The area ratio of hard structure is 90% or more, and the Vickers hardness of the steel is 250 to 450 HV. (Feature 3) 0.0005μm in hard tissue 2 The number density ND of cementite having an area of ​​4.0 / μm 2 or more, and 0.0005 μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the area of ​​multiple cementites having an area of ​​0.070 μm or more 2 The following is the result. When the steel material having the above-mentioned configuration is used as a bolt material, it is possible to reduce the hydrogen embrittlement susceptibility of the bolt.

[0097] [Method for evaluating hydrogen embrittlement susceptibility] In this specification, hydrogen embrittlement susceptibility is evaluated, for example, by the following method. The steel material of this embodiment is subjected to wire drawing. The drawn steel material is subjected to well-known spheroidizing annealing. In the spheroidizing annealing, the steel material is heated to 760°C. Then, the steel material is held at 760°C for 5.0 hours. After the holding time has elapsed, the steel material is slowly cooled to 650°C at a rate of 7°C / hour. The steel material is air-cooled until the temperature of the steel material reaches between 650°C and room temperature.

[0098] The spheroidized annealed steel is subjected to cold forging (bolt forming) to manufacture an intermediate product in the shape of a bolt. The manufactured intermediate product is quenched and tempered under known conditions. The quenching temperature is 920°C, and the holding time at the quenching temperature is 1 hour. After the holding time has elapsed, the intermediate product is water-cooled. The quenched intermediate product is tempered. The tempering temperature is 620°C, and the holding time at the tempering temperature is 2.0 hours. Through the above steps, a bolt is manufactured.

[0099] A round bar test piece with a circular notch, measuring 7 mm in diameter and 70 mm in length, is taken from the inside of the manufactured bolt, at least 1 mm deep from the surface. A circular notch is formed in the center of the longitudinal direction of the test piece. The notch shape is 1.4 mm deep, the notch angle is 60°, and the radius of curvature at the notch base is 0.175 mm.

[0100] Hydrogen is charged to the circularly notched round bar test piece by the cathodic hydrogen charging method. Specifically, a cathodic hydrogen charging solution at room temperature is prepared. The cathodic hydrogen charging solution is an aqueous solution in which 3 g of ammonium thiocyanate is added to 1 L of a 3 mass % sodium chloride aqueous solution.

[0101] A round bar test piece with an annular notch was immersed in the cathodic hydrogen charging solution for 18 hours, and the cathodic current density was kept at 0.05 mA / cm. 2A constant current controlled at 1000 V is generated to add hydrogen to the annular notched round bar test specimen. After carrying out the cathodic hydrogen charging method, the annular notched round bar test specimen is left at room temperature for 96 hours. After that, a zinc plating film is formed under the same conditions on the surface of the hydrogen-charged annular notched round bar test specimen to prevent hydrogen from leaking out from the annular notched round bar test specimen.

[0102] A constant load test is carried out at room temperature and atmospheric pressure, applying a constant load to a round bar test piece with an annular notch on which a zinc plating film is formed, so that a load of cross-sectional area x tensile strength x 0.90 is applied. Here, the cross-sectional area refers to the cross-sectional area of ​​the cross section (transverse section) perpendicular to the longitudinal direction of the test piece at the bottom of the notch. Moreover, the tensile strength refers to the tensile strength (MPa) obtained by a tensile test described later using a smooth round bar tensile test piece.

[0103] The tensile test using the smooth round bar tensile test specimen is carried out in the following manner. A smooth round bar tensile test specimen is taken from the inside of the bolt, at least 1 mm deep from the surface. The diameter of the parallel part of the smooth round bar tensile test specimen is 6 mm, and the length of the parallel part is 70 mm. The central axis of the parallel part of the smooth round bar tensile test specimen is coaxial with the central axis of the bolt. A tensile test conforming to JIS Z 2241:2022 is carried out using the smooth round bar tensile test specimen in air at room temperature (20±15°C) to determine the tensile strength (MPa).

[0104] In the above-mentioned constant load test, if the round bar test piece with an annular notch can withstand 100 hours or more without fracture, it is determined that the hydrogen embrittlement susceptibility is sufficiently low. In the above-mentioned constant load test, the round bar test piece with annular notch of the steel material of this embodiment can withstand 100 hours or more without fracture. Therefore, the hydrogen embrittlement susceptibility of the bolt manufactured using the steel material of this embodiment as a material is sufficiently low.

[0105] [Steel shape] The steel material of this embodiment is a steel material having a circular cross section perpendicular to the axial direction (longitudinal direction). Specifically, it is a steel bar or wire having a circular cross section perpendicular to the axial direction. The steel material may be wound in a coil shape or cut to a predetermined length. The diameter of the cross section of the steel material of this embodiment is not particularly limited, but is, for example, 5 to 30 mm.

[0106] [Steel use] As described above, the steel material of this embodiment is suitable as a material for bolts. The steel material of this embodiment is particularly suitable as a material for bolts that have a tensile strength of 1600 MPa or more and require low hydrogen embrittlement susceptibility. However, the steel material of this embodiment may be used for applications other than the above-mentioned bolts.

[0107] [Steel manufacturing method] An example of a method for manufacturing the steel material of this embodiment will be described. The method for manufacturing the steel material described below is one example for manufacturing the steel material of this embodiment. Therefore, the steel material having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the steel material of this embodiment.

[0108] An example of a method for manufacturing a steel material according to this embodiment includes the following steps. (Process 1) Direct hot working process after casting (Process 2) Finish rolling process

[0109] The main production conditions in the above steps 1 and 2 are as follows. (Conditions for step 1) When the surface temperature of the casting material during cooling (solidification) reaches the range of 1100 to 900°C, hot working is performed on the casting material (direct hot working). (Conditions for step 2) ·Heating temperature HT: 1000~1200℃ Finish rolling temperature FT: 900℃ or higher Finish rolling temperature FT~820℃ Average cooling rate CR1: 1.0~2.0℃ / sec or less Average cooling rate from 820 to 400℃: CR2: 2.0 to 4.0℃ / sec

[0110] In the above-mentioned manufacturing process, the crystal grains in the steel are maintained as coarse as possible until the finish rolling is completed. As a result, during cooling after the finish rolling is completed, the bainite nose in the continuous cooling transformation diagram (CCT diagram) shifts to the long-time side. As a result, the transformation start temperature of bainite is lowered. If the transformation start temperature of bainite is lowered, the formation temperature of cementite that precipitates with bainite transformation is also lowered. If the formation temperature of cementite is lowered, the cementite is maintained fine. Therefore, a steel that satisfies Features 1 to 3 is manufactured. Each process will be explained below.

[0111] [(Process 1) Direct hot working process after casting] In the direct hot working process after casting, a cast material is produced, and when the surface temperature of the cast material during cooling (solidification) reaches a range of 1100 to 900°C, hot working is started to produce a billet. This makes it possible to produce a billet with coarse crystal grains.

[0112] The post-casting direct hot working process includes the following steps: (Step 11) Casting process (Process 12) Direct hot working process Each step will be described below.

[0113] [(Step 11) Casting process] In the casting process, a cast material having a chemical composition that satisfies Feature 1 is produced. Specifically, molten steel is prepared, the contents of each element in the chemical composition of which satisfy Feature 1. The prepared molten steel is used to produce a material by a well-known casting method. For example, an ingot is produced by an ingot casting method. Alternatively, a bloom is produced by a continuous casting method. Through the above steps, a cast material (ingot or bloom) is produced.

[0114] [(Process 12) Direct hot working process] In the direct hot working process, the cast material being cooled (solidified) after the casting process is subjected to hot working to produce a billet. Specifically, when the surface temperature of the cast material being cooled (solidified) falls within the range of 1100 to 900°C, hot working is started to produce a billet.

[0115] In this specification, the hot working is performed when the surface temperature of the cast material during cooling reaches 1100 to 900°C without cooling the produced cast material to room temperature. The hot working method may be hot forging or hot rolling. The cumulative reduction rate in the direct hot working step is not particularly limited, but is, for example, 35% or more.

[0116] Generally, the casting material produced by the casting method is first cooled to room temperature. Then, the casting material cooled to room temperature is heated in a heating furnace. c3 The cast material is heated to above the transformation point, and then blooming (rough rolling) is performed. In this specification, this conventional manufacturing process is referred to as "hot processing after reheating." In the case of hot processing after reheating, reverse transformation (transformation from α phase to γ ​​phase) occurs in the cast material during heating before blooming. This reverse transformation refines the crystal grains.

[0117] On the other hand, in the present embodiment, the grain refinement caused by the reverse transformation is avoided. Specifically, when the surface temperature of the casting material during cooling in the casting process is within the range of 1100 to 900°C, that is, when the surface temperature of the casting material is A r3 The billet is manufactured by hot forging or hot rolling the cast material at or above the transformation point. In this case, the cast material is hot worked without reverse transformation, so that the grains of the manufactured billet can be prevented from being refined. The upper limit of the cumulative rolling reduction in the direct hot working step is not particularly limited, but is, for example, 80%.

[0118] [(Process 2) Finish rolling process] In the finish rolling process, the billet produced in the direct hot working process is heated. The heated billet is finish rolled. The finish rolled billet is cooled to produce a steel material. In the finish rolling process, the following manufacturing conditions are satisfied. The conditions in the finish rolling process are as follows: ·Heating temperature HT: 1000~1200℃ Finish rolling temperature FT: 900℃ or higher Finish rolling temperature FT~820℃ Average cooling rate CR1: 1.0~2.0℃ / sec or less Average cooling rate from 820 to 400℃: CR2: 2.0 to 4.0℃ / sec Each production condition will be explained below.

[0119] [About heating temperature HT] The heating temperature HT in the heating furnace in the finish rolling process is 1000 to 1200°C. If the heating temperature HT of the heating furnace in the finish rolling process is less than 1000°C, the precipitates in the billet do not dissolve sufficiently. In this case, the undissolved precipitates have a pinning effect, which suppresses the coarsening of crystal grains in the billet. In this case, the cementite in the steel material after the finish rolling process becomes coarse, and Feature 3 is not satisfied. On the other hand, if the heating temperature HT exceeds 1200° C., the manufacturing cost increases. Furthermore, cracks are likely to occur in the billet during finish rolling. Therefore, the heating temperature HT is 1000 to 1200°C.

[0120] The lower limit of the heating temperature HT is preferably 1020°C, more preferably 1040°C, and further preferably 1060°C. The upper limit of the heating temperature HT is preferably 1180°C, more preferably 1160°C, and further preferably 1140°C. The holding time at the heating temperature HT is not particularly limited and is, for example, 0.5 to 4.0 hours.

[0121] [About the finishing rolling temperature FT] In the finish rolling process, hot rolling (finish rolling) is performed by a continuous rolling mill equipped with multiple rolling stands arranged in a row. In hot rolling using a continuous rolling mill, the temperature of the steel material at the outlet side of the stand that lastly rolled down the steel material is defined as the finish rolling temperature FT (°C). The steel material temperature means the surface temperature of the steel material.

[0122] The finish rolling temperature FT is 900°C or higher. If the finish rolling temperature FT is less than 900° C., the pinning effect of precipitates suppresses the coarsening of crystal grains in the steel material. In this case, the cementite in the steel material after the finish rolling process becomes coarse, and characteristic 3 is not satisfied.

[0123] If the finish rolling temperature is 900°C or higher, the crystal grains after finish rolling can be maintained in a coarse state. As a result, fine cementite can be produced in the subsequent cooling process, and Feature 3 is satisfied.

[0124] [Cooling after finish rolling] After the finish rolling is completed, the finish-rolled steel is cooled. By satisfying the manufacturing conditions in the above-mentioned process, the crystal grains in the finish-rolled steel are maintained as coarse grains. Therefore, in the steel having the chemical composition of Feature 1, the bainite nose in the CCT diagram is shifted to the long-term side. In other words, the transformation start temperature of bainite is lowered.

[0125] Therefore, in the cooling after finish rolling, when the steel material temperature is in the range of the finish rolling temperature FT to 820°C, the cooling rate (average cooling rate CR1) is made as slow as possible to maintain the crystal grains as coarse as possible. In addition, when the steel material temperature is in the range of 820 to 400°C, which corresponds to the bainite transformation temperature range, the cooling rate (average cooling rate CR2) is made faster to suppress the growth of cementite that is generated with the bainite transformation. The average cooling rates CR1 and CR2 are explained below.

[0126] [About the average cooling rate CR1] The average cooling rate CR1 means the arithmetic average value of the cooling rate in the range in which the steel temperature is from the finish rolling temperature FT to 820°C.

[0127] If the average cooling rate CR1 is 2.0°C / sec or more, the cooling rate in this temperature range is too fast. In this case, the crystal grains in the steel become finer. As a result, the bainite nose shifts to the short-time side in the CCT diagram for the steel with the chemical composition of Feature 1. In this case, the bainite transformation temperature becomes higher. As a result, the cementite that is generated by the bainite transformation grows during cooling. As a result, the steel after the finish rolling process does not satisfy Feature 3.

[0128] The lower limit of the average cooling rate CR1 is not particularly limited. Taking into consideration the equipment capacity, the lower limit of the average cooling rate CR1 is 1.0° C. / sec.

[0129] The lower limit of the average cooling rate CR1 is preferably 1.1° C. / sec, and more preferably 1.2° C. / sec. The upper limit of the average cooling rate CR1 is preferably 1.9° C. / sec, and more preferably 1.8° C. / sec.

[0130] [About the average cooling rate CR2] The average cooling rate CR2 means the arithmetic average value of the cooling rate in the range from 820°C to 400°C of the steel material temperature.

[0131] The temperature range of 820 to 400°C includes the temperature range in which bainite transformation occurs in a steel material produced by using a cast material having a chemical composition that satisfies the characteristic 1 and by satisfying the above-mentioned production conditions. Therefore, in the temperature range of 820 to 400°C, the cooling rate is increased to a degree that does not cause excessive formation of martensite. This suppresses the growth of cementite that is produced during bainite transformation, and maintains the cementite in a fine state.

[0132] When the average cooling rate CR2 is less than 2.0° C. / sec, the cooling rate in the temperature range of 820 to 400° C. is too slow. In this case, the cementite formed becomes coarse. As a result, the steel material after the finish rolling process does not satisfy Feature 3.

[0133] On the other hand, when the average cooling rate CR2 exceeds 4.0°C / sec, the cooling rate in the temperature range of 820 to 400°C is too fast. In this case, martensite is generated excessively. As a result, in the microstructure of the steel material after the finish rolling process, the area ratio of the hard structure is 90% or more, but the Vickers hardness exceeds 450HV.

[0134] If the average cooling rate CR2 is 2.0 to 4.0° C. / sec, the steel material after the finish rolling process satisfies Features 1 to 3, provided that other manufacturing conditions are met.

[0135] The lower limit of the average cooling rate CR2 is preferably 2.2° C. / sec, more preferably 2.4° C. / sec, and even more preferably 2.6° C. / sec. A preferred upper limit of the average cooling rate CR2 is 3.8° C. / sec, more preferably 3.6° C. / sec, and even more preferably 3.4° C. / sec.

[0136] The average cooling rates CR1 and CR2 can be calculated by the following method. Cooling of the steel material is carried out in a cooling equipment line arranged downstream of the continuous rolling mill that performs the finish rolling. Thermometers are set at multiple locations on the cooling equipment line from upstream to downstream. The steel material temperature as it passes through each thermometer and the passing time are detected. The average cooling rates CR1 and CR2 are calculated based on the obtained steel material temperature and passing time.

[0137] The steel material of this embodiment is manufactured by the above manufacturing process.

[0138] [Bolt manufacturing process] For reference, a manufacturing process for a bolt made of the steel material of this embodiment will be described. An example of the manufacturing process for a bolt made of the steel material of this embodiment includes the following steps. Note that the manufacturing process for a bolt is well known. ·Wire drawing process Spheroidizing annealing process Cold forging process ·Quenching and tempering process Each step will be described below.

[0139] [Wire drawing process] In the wire drawing process, the above-mentioned steel material is subjected to a well-known wire drawing process to manufacture a steel wire. The wire drawing process may be a primary wire drawing process only, or may be a multiple-step wire drawing process such as a secondary wire drawing process.

[0140] [Spheroidizing annealing process] In the spheroidizing annealing process, the steel wire after the wire drawing process is subjected to spheroidizing annealing. The spheroidizing annealing may be performed under well-known conditions. For example, the steel wire is heated to 720 to 800°C. Then, it is held at 720 to 800°C for 1.0 to 6.0 hours. Then, it is slowly cooled to 650°C at a cooling rate of 3 to 10°C / hour. Then, it is cooled to room temperature.

[0141] [Cold forging process] In the cold forging process, the steel wire after the spheroidizing annealing process is subjected to known cold forging to manufacture an intermediate product in the shape of a bolt.

[0142] [Quenching and tempering process] In the quenching and tempering process, the intermediate product is quenched and tempered.

[0143] [Hardening] The intermediate product after the cold forging process is quenched by a known method. The quenching temperature and the holding time at the quenching temperature are not particularly limited. The quenching temperature is, for example, 900 to 1050°C. The holding time at the quenching temperature is, for example, 15 minutes to 360 minutes (6 hours). After the holding time has elapsed, the intermediate product is quenched. Specifically, the intermediate product is water-cooled or oil-cooled.

[0144] [Tempering] The intermediate product after quenching is subjected to a known tempering process. The tempering conditions are, for example, as follows: the tempering temperature is, for example, 570 to 660° C. The holding time at the tempering temperature is, for example, 0.5 to 6.0 hours.

[0145] By the above-described manufacturing method, a bolt made of the steel material of this embodiment can be manufactured.

[0146] [Other processes] The manufacturing process of the bolt may include other steps in addition to the steps described above. For example, a rolling process may be performed after the cold forging process and before the quenching and tempering process to form a thread. Furthermore, a compressive residual stress imparting process may be performed after the quenching and tempering process. All of these steps are optional and may not be performed. EXAMPLES

[0147] The effect of the steel material of this embodiment will be described more specifically with reference to examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effect of the steel material of this embodiment. Therefore, the steel material of this embodiment is not limited to this one example of conditions.

[0148] Steel materials (round bars) were prepared for bolts, with the chemical compositions shown in Tables 1-1 and 1-2. In the tables, "-" indicates that no additive was intentionally added.

[0149] [Table 1-1]

[0150] [Table 1-2]

[0151] The steel materials of each test number were produced by the following method: Ingots having the chemical compositions shown in Tables 1-1 and 1-2 were produced by a casting method (casting process).

[0152] In test numbers 1 to 22 and 25 to 32, when the surface temperature of the cast material during cooling after the casting process reached 1100 to 900°C, hot forging was performed on the cast material to produce billets. That is, in these test numbers, direct hot working was performed (listed as "direct" in the "hot working" column in Table 2). On the other hand, in test numbers 23 and 24, the cast material was cooled to room temperature, reheated to 1200°C in a heating furnace, and then hot forging was performed to produce billets (listed as "after reheating" in the "hot working" column in Table 2). In all hot working methods, the cumulative reduction in the direct hot working process was within the range of 35 to 60%.

[0153] [Table 2]

[0154] The produced billet (162 mm x 162 mm cross section) was subjected to a finish rolling process to produce a steel material (round bar) with a diameter of 20 mm.

[0155] The heating temperature HT (°C) in the finish rolling process, the finish rolling temperature FT (°C), the average cooling rate CR1 (°C / sec) at which the steel temperature was changed from the finish rolling temperature FT to 820°C, and the average cooling rate CR2 (°C / sec) at which the steel temperature was changed from 820°C to 400°C were as shown in Table 2. Steel materials (round bars) of each test number were manufactured by the above manufacturing process.

[0156] [Evaluation test] The manufactured steel materials were subjected to the following evaluation tests. (Test 1) Microstructure observation test (Test 2) Vickers hardness test (Test 3) Measurement test of cementite number density ND, cementite number ratio NR and sample standard deviation σ (Test 4) Steel wiredrawability evaluation test (Test 5) Cold forgeability evaluation test of steel (Test 6) Hydrogen embrittlement susceptibility evaluation test for steel bolts Each evaluation test will be described below.

[0157] [(Test 1) Microstructure Observation Test] The area ratio (%) of the hard structure in the microstructure of the steel material of each test number was determined based on the above-mentioned [Method of measuring the microstructure of steel material]. The obtained results are shown in the "Area ratio (%) of hard structure" column in "Microstructure" in Table 2.

[0158] [(Test 2) Vickers hardness test] The Vickers hardness (HV) of the steel material of each test number was determined based on the above-mentioned [Vickers hardness measurement method]. The obtained Vickers hardness (HV) is shown in the "Vickers hardness (HV)" column in the "Microstructure" section of Table 2.

[0159] [(Test 3) Measurement test of cementite number density ND, cementite number ratio NR, and sample standard deviation σ] For each test number, 0.0005μm of hard structure 2 The number density ND (pieces / μm 2 ), 0.0005 μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR (%) of cementite having an area of ​​0.0005 μm in the hard structure 2 The sample standard deviation σ(μm 2 ) was obtained based on the above-mentioned [Method of measuring the number density ND of cementite, the number ratio NR of cementite, and the sample standard deviation σ of the area of ​​cementite]. The obtained number density ND (pieces / μm 2 ), number ratio NR (%) and sample standard deviation σ (μm 2 ) in the "Cementite" column in Table 2, "Number density ND (pieces / μm 2 ), "Number ratio NR (%)" and "Sample standard deviation σ (μm 2 )" column.

[0160] [(Test 4) Steel wiredrawability evaluation test] The following wiredrawing process was carried out on the steel material with each test number. 250 kg of steel material with each test number was subjected to lubrication treatment under the same conditions, and then wiredrawing process was carried out. The cumulative reduction in area of ​​the die during wiredrawing process was set to 25%. If no breakage occurred during wiredrawing process, the wiredrawability was evaluated as excellent (shown as "P (Pass)" in the "Wiredrawability" column in Table 2). On the other hand, if breakage occurred during wiredrawing process, the wiredrawability was evaluated as poor (shown as "F (Fail)" in the "Wiredrawability" column in Table 2). Note that tests 5 and 6 were not carried out on the steel material with test numbers that had poor wiredrawability.

[0161] [(Test 5) Cold forgeability evaluation test of steel] The cold forgeability of the steel material having each test number was evaluated by the following method. First, the steel material was subjected to spheroidizing annealing. In the spheroidizing annealing, the steel material was heated to 760°C. Then, the steel material was held at 760°C for 5.0 hours. After the holding time had elapsed, the steel material was slowly cooled to 650°C at 7°C / hour. The steel material was air-cooled from 650°C to room temperature.

[0162] A smooth test piece was taken from the D / 4 depth position in the cross section perpendicular to the longitudinal direction of the steel material after spheroidizing annealing. The smooth test piece was cylindrical, with a diameter of 8 mm and a length of 12 mm. The longitudinal direction of the smooth test piece was parallel to the longitudinal direction of the steel material.

[0163] A limit compression test was carried out on the smooth test piece in accordance with the test method described in Cold Forging Subcommittee Materials Research Group: Plasticity and Processing vol. 22 No. 241 (1981-2), pages 139-144. Specifically, the smooth test piece was cold compressed at room temperature in air at a speed of 10 mm / min using an end face restraint die. When microcracks of 0.5 mm or more were formed in the smooth test piece, the compression was stopped and the compression ratio (%) at that time was calculated. This measurement was carried out a total of 10 times, and the compression ratio (%) at which the cumulative breakage probability was 50% was determined, and this compression ratio was taken as the limit compression ratio (%).

[0164] When the limit compression ratio was 60% or more, it was determined that the cold forgeability was excellent (shown as "60 or more" in the "Limit compression ratio (%)" column in Table 2). On the other hand, when the limit compression ratio was less than 60%, it was determined that the cold forgeability was poor (shown as the limit compression ratio (%) in the "Limit compression ratio (%)" column in Table 2).

[0165] [(Test 6) Hydrogen embrittlement susceptibility evaluation test for steel bolts] The hydrogen embrittlement susceptibility evaluation test of the bolts made of the steel material having each test number was performed by the following method.

[0166] First, the steel material of each test number was subjected to wire drawing under the same conditions to produce a steel wire with a diameter of 16 mm. The steel wire of each test number was subjected to spheroidizing annealing under the same conditions as those in the spheroidizing annealing performed in [(Test 5) Steel material cold forgeability evaluation test]. The steel wires after spheroidizing annealing were subjected to cold forging (bolt forming) under the same conditions to produce intermediate products having the same bolt shape and a thread root diameter of 14 mm for each test number.

[0167] The intermediate products were quenched and tempered. For quenching, the quenching temperature was 920°C and the holding time at the quenching temperature was 1 hour for each test number. After the holding time had elapsed, the intermediate products were water-cooled.

[0168] The intermediate products after quenching were tempered at a tempering temperature of 620°C for a holding time of 2.0 hours. Bolts with each test number were manufactured according to the above manufacturing process.

[0169] A tensile test and a constant load test were carried out on the bolts with each test number according to the method described in [Method of evaluating hydrogen embrittlement susceptibility]. The tensile strength obtained by the tensile test is shown in the "Tensile strength (MPa)" column in "Hydrogen embrittlement susceptibility" in Table 2. The maximum test time for the constant load test was 100 hours. In the constant load test, if the round bar test specimen with an annular notch lasted for 100 hours or more without fracture, it was evaluated as having sufficiently low hydrogen embrittlement susceptibility (shown as "100 or more" in the "Duration time (hours)" column under "Hydrogen embrittlement susceptibility" in Table 2). On the other hand, if the round bar test specimen with annular notch fractured in less than 100 hours in the constant load test, it was evaluated as having high hydrogen embrittlement susceptibility (shown as the durability time (hours) in the "Duration time (hours)" column under "Hydrogen embrittlement susceptibility" in Table 2).

[0170] [Evaluation Results] With reference to Tables 1-1, 1-2, and 2, the steel materials of test numbers 1 to 22 had appropriate chemical compositions and appropriate manufacturing conditions. Therefore, the area ratio of the hard structure was 90% or more, and the Vickers hardness was 250 to 450 HV. Furthermore, the area ratio of the hard structure of the steel materials of 0.0005 μm 2 The number density ND of cementite having an area of ​​4.0 / μm 2 or more, and 0.0005 μm in hard tissue 2 Among the multiple cementites having an area of ​​0.0005 to 0.0100 μm or more, 2 The number ratio NR of cementite having an area of ​​0.0005 μm or more in the hard structure is 50.0% or more. 2 The sample standard deviation σ of the areas of multiple cementites having an area of ​​0.070 μm 2 The wire drawing processability was therefore excellent. Furthermore, the cold forgeability after spheroidizing treatment was excellent. Furthermore, the hydrogen embrittlement susceptibility of the bolts manufactured using the steel material was sufficiently low.

[0171] In test numbers 23 and 24, the chemical composition was appropriate, but the cast materials were reheated and then hot worked. As a result, the cementite number density ND was 4.0 particles / μm. 2 The cementite number ratio NR is less than 50.0%, and the sample standard deviation σ of the cementite area is 0.070 μm 2 As a result, bolts made from steel were highly susceptible to hydrogen embrittlement.

[0172] In test numbers 25 and 26, the chemical composition was appropriate, but the heating temperature HT in the finish rolling process was too low, and the finish rolling temperature FT was too low. As a result, the number density ND of cementite was 4.0 pieces / μm 2 The cementite number ratio NR is less than 50.0%, and the sample standard deviation σ of the cementite area is 0.070 μm 2 As a result, bolts made from steel were highly susceptible to hydrogen embrittlement.

[0173] In test numbers 27 and 28, the chemical composition was appropriate, but the average cooling rate CR1 was too fast. As a result, the number density ND of cementite was 4.0 particles / μm. 2 The cementite number ratio NR is less than 50.0%, and the sample standard deviation σ of the cementite area is 0.070 μm 2 As a result, bolts made from steel were highly susceptible to hydrogen embrittlement.

[0174] In test numbers 29 and 30, the chemical composition was appropriate, but the average cooling rate CR2 was too slow. As a result, the number density ND of cementite was 4.0 particles / μm 2 The cementite number ratio NR is less than 50.0%, and the sample standard deviation σ of the cementite area is 0.070 μm 2 As a result, bolts made from steel were highly susceptible to hydrogen embrittlement.

[0175] In test numbers 31 and 32, although the chemical composition was appropriate, the average cooling rate CR2 was too fast. As a result, although the area ratio of the hard structure was 90% or more, the Vickers hardness exceeded 450HV. Therefore, the wire drawability was poor.

[0176] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.

Claims

1. In mass percent, C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10 to 1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Mo: more than 2.50 to 3.50%, V: 0.01-0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, The balance is Fe and impurities. The area ratio of the hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV; 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 pieces / μm 2 or more, and among the plurality of cementites in the hard structure, 0.0005 to 0.0100 μm 2 The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 Below is the Steel material.

2. In mass percent, C: 0.30-0.50%, Si: 0.01-0.30%, Mn: 0.10 to 1.50%, P: 0.030% or less, S: 0.030% or less, Cr: 0.01-0.30%, Mo: more than 2.50 to 3.50%, V: 0.01-0.50%, Al: 0.005 to 0.100%, and N: 0.0010 to 0.0300%, Further, the composition contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The area ratio of the hard structure is 90% or more, and the Vickers hardness is 250 to 450 HV; 0.0005 μm in the hard tissue 2 The number density of cementite having an area of ​​4.0 pieces / μm 2 or more, and among the plurality of cementites in the hard structure, 0.0005 to 0.0100 μm 2 The number ratio of the cementite having an area of ​​50.0% or more, and the sample standard deviation of the areas of the cementite in the hard structure is 0.070 μm 2 Below is the Steel material. [Group 1] Cu: 0.40% or less, Ni: 0.40% or less, B: 0.0100% or less, Zr: 0.300% or less, Hf: 0.100% or less, Ta: 0.100% or less, and W: 0.200% or less, one or more selected from the group consisting of [Group 2] Ti: 0.100% or less, and Nb: 0.100% or less, one or more selected from the group consisting of [Group 3] Ca: 0.0050% or less, and Mg: 0.0050% or less, one or more selected from the group consisting of [Group 4] Bi: 0.020% or less; and Te: 0.010% or less, one or more selected from the group consisting of

3. The steel material according to claim 2, Containing the first group, Steel material.

4. The steel material according to claim 2, Containing the second group, Steel material.

5. The steel material according to claim 2, Containing the third group, Steel material.

6. The steel material according to claim 2, Containing the fourth group Steel material.

Citation Information

Patent Citations

  • Bolt, and steel material for bolts

    WO2020162616A1